SOSIALISASI DAMPAK ILMUWAN KEPADA MASYARAKAT SEBAGAI WUJUD KEMANDIRIAN BANGSA - Martiman S. Sarumaha (Universitas Nias Raya, 2023)
The purpose of this service activity is to provide understanding and awareness for the community that the impact of someone who has earned a bachelor's degree to become a scientist in society and to be able to understand and realize that he is in the midst of society can be useful as a form of national independence. The method used in this service is the lecture method in the form of outreach which is conveyed through scientific orations to the academic community and the wider community. The results obtained in the service carried out are that through this socialization the campus community and the general public can understand and understand that they are the most important part of society, the progress and decline and development of a village depends on graduates who have graduated from tertiary institutions who pass on their knowledge in the midst of - in the midst of society to become an independent generation for the nation and state. The conclusion of this service activity is that alumni and academics who already know their identity as quality individuals and become scientists who return to society as a form of national independence make the community where they live prosperous.